Scientific Publication Patterns of Interactive Mobile Technologies for Psychological, Social, Medical and Business Interventions for Mental and Physical Health: Bibliometric Analysis - Shubina, Ivanna (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Abstract - There has been emerging interest in the effectiveness of interactive mobile technology usage in psychological, social, medical and business interventions. However, the field still lacks holistic overviews of the role of technology for psychological, social, medical and business interventions. The present bibliometric study was employed to identify and synthesize the results from studies exploring domains of interactive mobile technology used in applied psychology and counseling, supporting health professionals, managing mental and physical health, humanizing technology and improving its efficiency in the business field, as well as in the social field including vocational education, safeguarding, communities and ethnic minorities. An author analyzed the papers published in highly ranked and cited journals which were indexed and ranked in the Web of Science Core Collection and Scopus, in the period of 2020 to 2021. The results demonstrated high interest in studied domains within various subjects and fields of study, demonstrating the interest in the opportunities which provide the technology for professional education and developing methodological competences.